Komodifikasi Berita pada Newsroom Terintegrasi iNews TV Semarang - Indira Ayudhia Maharani; Nurul Hasfi (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2020)
iNews TV Semarang is a local television station under the corporation of the MNC Group along with RCTI Network Jawa Tengah and MNC TV Semarang. The MNC Group’s desire to decrease the operational costs of its local television station in Central Java then brought up an integration system for local television in Semarang that consists of iNews TV Semarang, RCTI Network Jawa Tengah, and MNC TV Semarang. This integration system means that those local television stations have to share their newsroom in the same building. With the high demand for news on third television, the commodification of news has emerged as a solution to limited resources owned by the integrated newsroom of iNews TV Semarang. The form of news commodification can be seen from some similar news that are broadcasted on the three televisions. In principle, this commodification practice violates the principle of diversity of content, which demands a content diversity from various televisions. The existence of local television which is regulated in Undang-Undang Nomor 50 tahun 2005 concerning Private Institution Broadcasting is actually intended to create diversity of content on various existing private television stations. In this case, the news as the object of commodification and similarly displayed on the three MNC Group televisions shows that there is no diversity of content, so the principle of diversity of content is not fulfilled. This study was designed to describe the process of news commodification in the integrated newsroom at iNews TV Semarang. In analyzing the process of commodification, this study uses the concept of commodification in the Political Economy Theory by Vincent Mosco. This research uses a critical theory paradigm with a descriptive type and uses a case study method. The results of this study were obtained by conducting interviews with 6 informants involved in the news commodification process in the integrated newsroom iNews TV Semarang. In addition, the results of this study were also obtained from researchers' observations to the media routines of iNews TV Semarang, specifically in the news production process. The results showed that there are four patterns of commodification that happened in the integrated newsroom at iNews TV Semarang. First, the commodification of content as an effort to increase use value, where news can be used by all three televisions at once which are iNews TV Semarang, MNC TV Semarang, and RCTI Network Jawa Tengah. Second, the commodification of content as an effort to increase the exchange rate where news is transformed into something that can provide benefits for the newsroom. Third, immanent commodification as an effort to combine some different commodities, which are the news, into a new commodity or news.